Association of starch crystalline pattern with acetylation property and its influence on gut microbota fermentation characteristics. (July 2022) - Wang, Rui; Wang, Jing; Liu, Min; Strappe, Padraig; Li, Mei; Wang, Anqi; Zhuang, Min; Liu, Jinguang; Blanchard, Chris; Zhou, Zhongkai
Abstract: The aim of this study was to investigate the relationship between starch structure characteristics and the degree of acetylation and further reveal the in vitro fecal fermentation characteristics of polycrystalline polymers. The current study indicated that potato starch (POS, B-type) and pea starch (PS, C-type) were more prone to be acetylated than rice starch (RS, A-type) under the same reaction conditions. The degree of substitution were 0.0513 (RS), 0.0993 (POS) and 0.0604 (PS), respectively. Consistently, acetylation led to B-type crystalline region to have a greatest damage followed by C and A-type starch, accompanied by a decrease in thermodynamic stability. Acetylation reduces the surface pore structure and more short-chain fatty acids content produced compared to the native starch granules following microbiome fermentation, suggesting that the introduced acetyl groups influenced the digestion and fermentation behavior of the starch granules. In addition, A-type starch was fermented at faster rate by the gut bacteria microbiota and acylated starch was more easily utilized by gut microbiota. We conclude that the type of polycrystalline polymer and the surface structure of the granules mainly affect the fecal fermentation rate and the spiral stacking mode is the key factor affecting the acetylation ability. Graphical abstract: Image 1 Highlights: B- and C-type starch was more vulnerable to acetylation than A-type starch granule. A-type starch was fermented at faster rate by the gut bacteria microbiota. Acetylated starch generated more SCFA than native starch by microbiota. Acetylation changed microbiota binding characters onto the starch granules. Crystalline and helical structure were related to acetylation and fermentation.